Design and development of a modular ballistic pendulum for high‐impulse measurement in contact and near‐field explosive loading - Alford, Roland; Hazael, Rachael; Critchley, Richard; Humphreys, Lisa (Wiley, 2026)
Measuring impulse from explosive charges in contact and near‐field configurations presents practical challenges due to wide variation in impulse magnitude. Ballistic pendula are widely used for impulse measurement, but many existing designs are limited to narrow operating envelopes or are poorly suited to repeated contact testing and tamped charge configurations. This paper describes the design of a modular ballistic pendulum (MBP) for measuring explosive impulse in contact and near‐field configurations; experimental validation and impulse behaviour are addressed in companion papers. The apparatus employs a horizontal pendulum configuration with interchangeable masses on a single supporting frame, allowing the measurement range to be adapted to different net explosive quantities. A review and classification of existing ballistic pendulum designs is presented to justify the selected configuration. The apparatus design and geometric operating limits are described. The geometric limits of the apparatus are examined to determine the maximum effective stand‐off distance for which measurements remain representative, governed by the relationship between blast footprint and striker plate area. The resulting apparatus provides a repeatable, reconfigurable platform spanning approximately 2–2000 N·s, with defined geometric constraints and practical tolerances for contact and near‐field charge testing.
Keywords: Chemical Physics; 4004 Chemical engineering; ballistic pendulum; experimental apparatus; explosive testing; high-strain-rate measurement; impulse measurement; modular design; near-field loading